THE CONSEQUENCES OF SUPERVISORY LAW ON THE REGIONAL REGULATIONS WITH LOCAL CHARACTERISTICS - Victor Juzuf Sedubun (Yustisia, 2018)
The present study investigates the consequences of supervisory law on the regional regulations with local characteristics. The study is normative with regards to the commandment and conceptual approaches. The consequences of supervisory law on the regional regulations with local characteristics, according to Article Number 251 verse 1 and 2, are dismissed (‘vernietigbaar’). ‘Vernietigbaar’ is ‘ex nunc’ that means ‘since the moment’. As a consequence of the law, the dismissal of regional regulations is valid until it is issued by the regional government. Due to the existing supervisory law performed by the Supreme Court, the judge declares the regional regulations ‘invalid’ since they are lack of powerful relevant laws. The Regional Government took a legal action on the issue of dismissed regional regulations by submitting an objection to the Supreme Court.